PENGEMBANGAN LKPD DIGITAL BERDIFERENSIASI PERILAKU LITERASI MATEMATIS BERBASIS MASALAH PADA MATERI LINGKARAN KELAS VIII SMP - Rahmawati, Rahmawati (Jurnal Edukasi dan Penelitian Matematika, 2024)
Digital learning resources that encourage diverse mathematical literacy behavior are the focus of this developmental research study. Eighth graders studying circular topics in junior high will find these resources based on valid, practical, and successful challenges. The Plomp development model is the one that is used for research development. Basic research, the prototype phase, and the assessment phase are the three separate parts that make up this paradigm. Results from tests, interviews, observations, and questionnaires made up the data set. A score of 84.6 percent was returned by the experts' validation of LKPD, suggesting that it is a very valid category. The practicality test phase was when LKPD was put to the test after it was determined to be viable. With an 87.58% score on the practicality test, it was deemed very practical. To find out how well LKPD worked, we used the mathematics literacy behavior test. Student test scores fell into the "regular" and "superior" categories, proving that the LKPD was successful.Keywords– Digital LKPD, Differentiated Mathematical Literacy Behavior, Problem Based